Comparison of relapse and treatment failure rates among patients with neuromyelitis optica: multicenter study of treatment efficacy. - Mealy, M; Wingerchuk, D; Palace, J; Greenberg, B; Levy, M (2014)
IMPORTANCE: Neuromyelitis optica (NMO) is an inflammatory disease of the optic nerves and spinal cord that leads to blindness and paralysis. Effective immunosuppression is the standard of care for relapse prevention. OBJECTIVE: To compare the relapse and treatment failure rates among patients receiving the 3 most common forms of immunosuppression for NMO: azathioprine, mycophenolate mofetil, and rituximab. DESIGN, SETTING, AND PARTICIPANTS: We performed a retrospective, multicenter analysis of relapses in 90 patients with NMO and NMO spectrum disorder treated with azathioprine, mycophenolate, and/or rituximab at the Mayo Clinic and the Johns Hopkins Hospital during the past 10 years. MAIN OUTCOME AND MEASURE: Annualized relapse rates. RESULTS: Rituximab reduced the relapse rate up to 88.2%, with 2 in 3 patients achieving complete remission. Mycophenolate reduced the relapse rate by up to 87.4%, with a 36% failure rate. Azathioprine reduced the relapse rate by 72.1% but had a 53% failure rate despite concurrent use of prednisone. CONCLUSIONS AND RELEVANCE: Initial treatment with rituximab, mycophenolate, and, to a lesser degree, azathioprine significantly reduces relapse rates in NMO and NMO spectrum disorder patients. Patients for whom initial treatment fails often achieve remission when treatment is switched from one to another of these drugs.